WORK STRESS RELATION WITH JOB SATISFACTION NON STAR HOTEL EMPLOYEES IN JAKARTA - wiwiek Robiatul Adawiyah (Media Riset Bisnis & Manajemen, 2005)
The purpose of the research is to acknowledge how much work stress level experienced by the non-star hotel employees and to analyze how the relationship between work stress factors which gave the largest contribution (dominant) to the non-star hotel employees satisfaction. The selected samples in the study consist of 37 local employees and 63 temporary employees from non-star hotel located in Jakarta, For local employees' sample, using senses method, while for temporary employees using proportioned stratified random sampling. To answer the purpose of this research we need to use the analyzes Rank-Superman methods. The hypotheses tested with Critical Ratio method. The veriable used is stress as independent variable which work consist from stress factors which developed by Hellriegel, Slocum, and Woodman, which career development, interpersonal relationship in the organization, and conflict between work and other roles. While dependent variable for this study is Job Descriptive Index. From this result of study data we conclude that The job level experienced by the employees of a non star hotel owned workload, job condition, role conflict, role ambiguity, me job by the government is low, which can be detected from the response of respondents against instruments of questions of work stress, where about 60,3 % respond are not in agreements. This research gave the same result with Robbins' theory which state that one of the stress impact psychologically can lower employees satisfaction. This study show that work stress relation/correlate resulted negatively to job satisfaction with the value Of r= 322 and level significant .001. From the analysis to the factor causing job stress and the relation to the work of the employee resulted in 2 factor causing stress which is work load and role conflict which is unsuccessful to show significant relation with employees jobsatisfaction. While other factors which is job condition, role ambiguity, career development, interpersonal relationship in the organization and conflict between work and other roles proven have significant relation for employees job satisfaction. The factor from most dominant job stress to employees job satisfaction is career development with the rate of = .1840 From the above conclusion, then we advise that company should be warned the work stress causing factors, high level work stress, since this work stress result can increase and decrease job satisfaction for the employees. It is advise that it must be looked on and reevaluate on the performance of employees career development. Since the responses from respondents showed that career development is the most dominant source of stress or biggest contribution in employees job satisfaction.